Dietary inclusion of mealworm frass: Effect on blood metabolites and growth performance of rabbits - Hanan A.M. Hassanein; Magdy H. Abou El-Fadel; Nabila E.M. El-Kassas; Youssef L. Phillip; Gustavo Tirado-Estrada; Abd-Alfattah A. Alderey; Amira S. EL-Deghadi; Ahmed M. Hussein; Mohamed A. Zayed; Mohamed A. Radwan; Maximilian Lackner; Abdelfattah Z.M. Salem (Journal of Agriculture and Food Research)
The effect of incorporating mealworm frass (MWF) in the diets of growing Gabaly rabbits on nutrient digestibility, live body weight and gain, properties of the carcass, and blood parameters was investigated. Fifty-two Gabaly rabbits (6 weeks old) were selected after weaning and divided into four groups in a random fashion (13 rabbits/group) based on their weights (653 ± 15 g). The experimental period extended from 6 to 15 weeks of age. Four isocaloric, isonitrogenous and isofibrous diets in pellet shape were formulated. Mealworm frass (MWF) was incorporated at levels of 0, 1, 2, and 3 % for rabbit groups: G0 (as a control), G1, G2, and G3. At the end of the feeding experiment period (15 weeks of age), digestibility trials were conducted to determine the nutrient digestibility and nutrition values of the experimental diets. Three rabbits were slaughtered from each group to determine the carcass traits and some blood parameters. The chemical composition MWF was recorded as dry matter 87.08-, organic matter 84.98-, crude protein 22.59-, crude fibre 17.62-, ether extract 2.78-, ash17.24-, and nitrogen-free extract 41.99- %. The digestibility of dry matter, organic matter, crude protein, and crude fibre improved (P <0.05) by an average of 12.3, 10.8, 11.4, and 60.6 %, respectively, in rabbits fed diets that contained MWF (G2 and G3) compared to the control group. Moreover, the digestibility of ether extract was significantly higher in G2 (85 %) compared with G1 (76.8 %) and G0 (76 %). While the digestibility of nitrogen-free extract was higher (P <0.05) in G3 (85.2 %) compared with G0 and G1 (78.3 and 77 %, respectively). The feeding value of total digestible nutrients and digestible energy increased by an average of 9.7 %, respectively, in G2 and G3 compared to G0. Including mealworm frass in growing rabbit diets led to numerical improvements in body weight, blood parameters, and carcass traits, though these changes were not statistically significant. Increasing the MWF content exhibited improvements in both relative and economic efficiency, with gains ranging from 5 to 40 %. These results suggested that MWF can be effectively integrated into rabbit diets up to 3 % without adverse effects, promoting both animal health and economic viability in rabbit production.